Effect of essential oils on ruminal fermentation, microbial population and methane emission in vitro - Sallam S.M.A.; Abdelgaleil S.A.M.; Bueno I.C.S.; Nassera M.E.A.; Araujo R.C.; Abdalla A.L. (Challenging strategies to promote the sheep and goat sector in the current global context, 2011)
The effect of adding increasing levels (0, 25, 50 and 75 µl/75 ml buffered rumen fluid) of essential oils (EOs) to a basal substrate (50 percent roughage: 50 percent concentrate) on ruminal fermentation characteristics was evaluated in vitro by a semi automatic gas production (GP) technique. The EOs used were from Achillea santolina (AS25, AS50, AS75), Artemisia judaica (AJ25, AJ50, AJ75), Schinus terebenthifolius (ST25, ST50, ST75) and Mentha microphylla (MM25, MM50, MM75). The main components of EO were piperitone (49.09 percent) and camphor (34.49 percent) in AJ, 1,6-dimethyle 1,5-cyclooactaiene (60.5 percent) in AS, piperitone oxide (46.7 percent), cis-piperitone oxide (28 percent) in MM and -murolene (45.25 percent), -thujene in ST. The administration of EOs affected (P<0.05) the cumulative gas production (GP). The AS50 increased (P<0.05) the GP but ST50, ST75 and all levels of MM decreased (P<0.05) the GP. The EOs from AS, AJ and ST increased (P<0.05) methane production with all investigated doses except AS75 which decreased it (P>0.05). The MM oils inhibited methane production along with a significant reduction of protozoa count. Partitioning factor (PF) was used as an index of the efficiency of microbial protein synthesis in vitro. There was no significant effect of EOs on PF except MM50 and MM75 which improved (P<0.05) the PF. The inclusion of AS, AJ and ST 25 did not affect (P>0.05) true digestibility of dry matter and organic matter, while ST50, ST75, MM50 and MM75 decreased (P<0.05) the true digestibility of dry matter and organic matter. The supplementation of AS75, ST50, ST75, MM50 and MM75 decreased (P<0.05)) protozoa population. The NH3-N concentration was dramatically declined with MM inclusion. This study suggested that EOs have the potential to affect ruminal fermentation efficiency. The EOs from MM and the third dose of AS75 could be a promising methane mitigating agent.
13. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2009/10/14-16, León (Spain)